Diet-Induced Obesity Mice Execute Pulmonary Cell Apoptosis via Death Receptor and ER-Stress Pathways after E. coli Infection. (28th June 2020) - Wang, Fengyuan; Zuo, Zhicai; Chen, Kejie; Fang, Jing; Cui, Hengmin; Geng, Yi; Ouyang, Ping; Chen, Zhengli; Huang, Chao; Guo, Hongrui; Liu, Wentao
Abstract : Obesity has developed into a considerable health problem in the whole world. Escherichia coli ( E. coli ) can cause nosocomial pneumonia and induce cell apoptosis during injury and infection. Normal (lean) and diet-induced obesity mice (DIO, fed with high-fat diet) were chosen to perform nasal instillation with E. coli to establish a nonfatal acute pneumonia model. At 0 h, 12 h, 24 h, and 72 h postinfection, lung tissues were obtained to measure cell apoptosis. As shown in this study, both lean and DIO mice exhibited histopathological lesions of acute pneumonia and increased cell apoptosis in the lung infected with E. coli . Interestingly, the relative mRNA and protein expressions associated with either endoplasmic reticulum stress or death receptor apoptotic pathway were all dramatically increased in the DIO mice after infection, while only significant upregulation of death receptor apoptotic pathway in the lean mice at 72 h. These results indicated that the DIO mice executed excess cell apoptosis in the nonfatal acute pneumonia induced by E. coli infection through endoplasmic reticulum stress and death receptor apoptotic pathway.